Intravenous Methylprednisolone, a Possible Cause of the Atrial Fibrillation: Atrial fibrillation by methylprednisolon - Afsaneh Vazin,; Gholamreza Rouzitalab,; Mohammad Firoozifar,; Farid Zand, (Iranian Journal of Pharmaceutical Sciences, 2010)
We are presenting a case illustrating atrial fibrillation (AF) following the use of methylprednisolone in a patient with pelvic and femur fracture. A48- year- old man with no significant past medical history, was admitted to the emergency department after injury in a car accident. He suffered a multiple bone fracture with chief complaints of pain and shortness of breath. He was transferred to the ICU. To prevent fat embolism syndrome, he was treated with methylprednisolone 500 mg every 6 h. About 4 h after the second dose, his normal sinus rhythm changed to a sinus tachycardia and then to AF. The methylprednisolone therapy was discontinued. After about 8 h of methylprednisolone discontinuation, the patient's normal sinus rhythm returned. Corticosteroids have been utilized for prevention and treatment of fat embolism syndrome, although there is uncertainty about their effectiveness. Cardiac dysrhythmias have been reported following the use of methylprednisolone. One possible mechanism of methylprednisolone induced AF is the direct effect on cell membrane, resulting in potassium efflux, which in turn, may initiate cardiac dysrhythmias. Previous methylprednisolone-associated AF case reports suggest a higher chance of AF occurrence with higher dose of methylprednisolone. Corticosteroids should be used with caution, especially when high doses are indicated and in patients with high risk for arrhythmias.